Cryptococcosis in HIV-infected hospitalized patients in Germany: Evidence for routine antigen testing. Issue 1 (July 2015) - Katchanov, Juri; Jefferys, Laura; Tominski, Daniela; Wöstmann, Kai; Slevogt, Hortense; Arastéh, Keikawus; Stocker, Hartmut
Summary Objectives To investigate the diagnostic value of routine cryptococcal antigen (CRAG) testing in HIV-infected patients in a low prevalence setting. Methods Retrospective single centre cohort study of a 10-year period (2005–2014). Results 5461 patients tested for CRAG were included. Cryptococcal antigenaemia was found in 1.6% and 1.1% of patients with CD4 counts of ≤100/μl and 101–200/μl, respectively. The positive predictive values for identifying clinically relevant cryptococcal disease was 96% and 100%, respectively. Half of the patients had a non-specific presentation and median time-to-diagnosis was high (5 days, range 1–44 days). The median time-to-diagnosis in direct admissions to our centre with routine CRAG testing was significantly shorter: 1 day (range: 1–17) vs. 7 days (range: 2–44), p = 0.003. Prevalence of cryptococcal antigenaemia was 2.8% in patients with pneumocystis pneumonia and median time-to-diagnosis of cryptococcosis was significantly longer in this subgroup (15 days; range: 1–44 vs. 3 days; range: 1–17; p = 0.008). CRAG titres ≥1:512 were associated with disseminated disease (OR 21.3, p = 0.0008, 95% CI 1.64–277), however, 10% of patients with disseminated cryptococcosis had CRAG titres <1:16. Conclusion Our data support routine CRAG testing in hospitalized HIV-infected patients with CD4 counts ≤200/μl, and/or pneumocystis pneumonia.